In Memoriam: Tetiana Andriivna Alifanova (Ukrainian Journal of Ophthalmology, 2025)
Tetiana Andriivna Alifanova, a wonderful person, a highly-skilled ophthalmologist and a talented scientist passed away on December 12, 2020.After graduating from the department of general medicine at Dnipropetrovsk Medical Institute of the Order of Red Banner of Labor in 1983, she was appointed to Dnipropetrovsk Institute for Restoration and Expertise of the Disabled Persons’ Ability to Work (DIREDPAW, currently, Ukrainian State Research Institute for Medical and Social Problems of Disability, USRIMSPD) and worked there until August, 2020.